2011
DOI: 10.1007/s10530-011-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Centaurea solstitialis invasion from annual and perennial grasses in California and Argentina

Abstract: A common explanation for Centaurea solstitialis invasion in California is that it occupies an ''empty niche'' created by the replacement of native perennial grasses by exotic annual grasses and concomitant increases in soil water availability. This hypothesis, however, cannot explain C. solstitialis invasion into perennial-dominated grasslands of central Argentina. We assessed invasibility of annual versus perennial grass communities in these regions through parallel field experiments where we created grass pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
6
15
1
2
Order By: Relevance
“…Previous studies have shown that invasibility of grassland communities, i.e. the susceptibility to being invaded, increases with disturbance (Hobbs 1989;Cano et al 2007;Hierro et al 2011). In the current study, we show a similar result.…”
Section: Hypothesis 2: Small-scale Disturbances Create Micro-sites Fosupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown that invasibility of grassland communities, i.e. the susceptibility to being invaded, increases with disturbance (Hobbs 1989;Cano et al 2007;Hierro et al 2011). In the current study, we show a similar result.…”
Section: Hypothesis 2: Small-scale Disturbances Create Micro-sites Fosupporting
confidence: 84%
“…Here, we present the results of a study designed to investigate how disturbance regimes can modify biotic resistance. Disturbance commonly promotes invasion success by temporarily reducing competition and, hence, biotic resistance of communities, thereby increasing their susceptibility to invasion (Hobbs & Huenneke 1992;Hierro et al 2006Hierro et al , 2011Cano et al 2007). The effects of disturbance are scale-dependent and can have long-lasting effects beyond the disturbance event itself.…”
Section: Introductionmentioning
confidence: 99%
“…Biotic resistance from the native community is a key factor controlling invasion success via competition, herbivory and/or pathogens (Elton, 1958;Levine, Adler, & Yelenik, 2004). Many studies on biotic resistance focus on the effect of competition during the early life stages (Cano, Escarre, & Sans, 2007;Eskelinen & Harrison, 2014;Hierro, Lortie, Villarreal, Estanga-Mollica, & Callaway, 2011;te Beest, Mpandza, & Olff, 2015;Thomsen, Corbin, & D'Antonio, 2006;Thomsen & D'Antonio, 2007). However, to what extent competition from resident communities affects survival and persistence during later life stages of long-lived woody plants is much less known.…”
Section: Introductionmentioning
confidence: 99%
“…We performed the study in the semiarid open forest of caldén (Prosopis caldenia, Fabaceae) in central Argentina, commonly known as the Caldenal (Cano et al 1980;Cabrera 1994). Similar to many natural systems around the world, most non-native invasive plants in the Caldenal are ruderals (sensu Grime 1974;Baker 1974;Mack et al 2000;Hierro et al 2005Hierro et al , 2006Hierro et al , 2011Pearson et al 2014a). Consequently, and in order to contrast native and non-native species with similar life-history strategies, we focused on comparing native vs. non-native ruderals.…”
Section: Introductionmentioning
confidence: 99%